Work from Home and Work Motivation of Teachers Job Satisfaction During Pandemic COVID-19 - Balasundran, Komathy; Nallaluthan, Kesavan; Yankteshery, Vijiyan; Harun, Kamarudin; Lim, Peck Poh; Gopal, Revathi (International Business Education Journal, 2021)
The magnitude of the Covid-19 epidemic has many features of teachers’ jobs, which affects teachers’ job satisfaction and work motivation, especially for those who work from home. This study aims to examine the relationship between work from home and work motivation on teachers’ job satisfaction. In addition, moderating the effects of school location on the relationships between work from home and motivational work on teachers’ job satisfaction is also investigated in this study. This study uses a quantitative approach. A purposive sampling technique is used to collect data from 424 respondents in this study. A web-based questionnaire is used as the research instrument. The data are analyzed using PLS-SEM by using SmartPLS 3.0 software. The study reveals that working from home and work motivation has a significant effect on teachers’ job satisfaction. In the interim, the school location does not moderate the relationships between work from home and work motivation on teachers’ job satisfaction. This study benefits the Malaysian Education Ministry, especially the training division, school leaders, and teachers in improving the efficiency of working from home and teachers’ motivation which can increase teachers’ job satisfaction.